Survival Outcomes in Patients after Radical Surgery for Non-Small Lung Cancer: an 8-year Study at N. N. Blokhin Cancer Research Center - Т. А. Bogush; Е. А. Rukavishnikova; А. А. Basharina; Е. А. Bogush; V. Yu. Kirsanov; S. D. Kolomiytsev; А. В. Ravcheeva; N. О. Vikhlyantseva; V. S. Kosorukov (Антибиотики и Химиотерапия)
In the study of 125 patients after radical surgery for non-small cell lung cancer (NSCLC), distinctive clinicopathological parameters of this disease were found. Thus, the majority of patients with NSCLC were smokers (73%), men had signiﬁcantly higher rate of the disease than women (80% vs 20%). Patients of diﬀerent sex varied by the tumor histological type: squamous cell carcinoma was characteristic of male patients (70%), while adenocarcinoma predominated in women (80%). Authors conclude that the described incidence patterns and the association of NSCLC with signiﬁcant clinical features are comparable with the literature data, which indicates the absence of signiﬁcant changes over the past 8 years. Survival rates of the patients after radical surgery for NSCLC also coincided with results of the previous studies. Overall survival rate varied by the stage of the disease, smoking status, and the tumor histological type: patients with earlier stage at diagnosis, never-smokers and patients with adenocarcinoma rather than squamous cell carcinoma were associated with a more favorable prognosis. The heterogeneity of the patients who survived 5 years after surgical treatment was shown: the group included patients not only with stage I of the disease, but also with more advanced II and even III stages of the disease. Finally, the absence of gender diﬀerences in the overall survival of the patients with NSCLC was demonstrated; this fact diﬀers from the literature data on the better survival of female patients compared to men. The authors suggest that the result may indicate the emergence of factors in the Russian population that improve the course of disease in men or adversely aﬀect the disease in women.